Relation between Serum Magnesium Level and Severity and Frequency of Migraine Headache Attacks - Ghasem Fattahzadeh Ardalani, Esmaeil Ghoryshi, Bahareh Javani (Journal of Applied Pharmaceutical Science, 2016)
The aim of this study was to assesses the relation between Serum Magnesium Level and Severity and Frequency of Migraine Headache Attacks. The study was performed on 100 patients those were divided randomly into two groups (Migraine patients and healthy patients each with 50 cases). For the first group (migraine patients) in addition to the usual migraine medication, magnesium oxide pills were prescribed and for healthy patients placebo was administered. Changes in the serum magnesium levels, severity and frequency of migraine headache attacks, one and three months after the start of the study were evaluated and collected data analyzed by statistical methods in SPSS.16. In migraine patients, 26% and in healthy patients, 30% were male and rests of them were female. All patients were aged 18-65 years. At one month and three months after intervention, the mean serum magnesium levels and headache severity was similar between two groups. One month later, reducing the number of headache attacks in the migraine patient was similar to the healthy patients but three months later, there was significant difference between two groups. (P= 0.004). Results showed that administration of magnesium can reduce the number of migraine attacks and can be more effective in preventing of disease.
Keywords: Migraines, magnesium, Headache.